PENGARUH LIKUIDITAS DAN STRUKTUR KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN DIVIDEN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Manufaktur Sub Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia (BEI) - Susilawati, Deti; Uzliawati, Lia; Fuadi, F (Pascasarjana Universitas Sultan Ageng Tirtayas, 2020)
This research is meat to analyze the effect of liquidity and institutional ownership on dividend policy with profitability as an intervening variable. The population in this study were sub-food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018 using annual financial statement data taken by purposive sampling, so that the results of 35 (thirty five) samples that met the criteria were obtained. The selected sampling criteria are 1) Sub-food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2018. 2) Sub-food and beverage manufacturing companies that distribute dividends in a row in the 2014-2018 period. The analysis technique used is multiple linear regression analysis and path analysis with a significant level of 5%, the results of this study indicate that: 1) Liquidity (CR) has no significant effect on dividend policy. 2) Institutional Ownership (IC) does not significantly influence dividend policy (DPR). 3) Profitability (ROA) has a positive and significant impact on dividend policy (DPR). 4) Profitability (ROA) is not able to mediate the effect of liquidity (CR) on dividend policy (DPR). 5) Profitability (ROA) is able to mediate the effect of Institutional Ownership (KI) on dividend po